Study guides

Q: 9x4 plus 27x3 - 4x2 - 12x equals 0?

Write your answer...

Submit

Related questions

4x2 = -12x, divide both sides by 4x: x = -3

4x2 + 12x + 5 = (2x + 1)(2x + 5).

(2x + 3)(2x + 3)

12x * 4x2 = 48x3

4x2+12x = 4x(x+3) when factored

Only if the value of c is 9 because:- 4x2+12x+9 = (2x+3)(2x+3)

4x2 - 12x + 9 = 5; whence, 2x - 3 = ±√5, and 2x = 3 ±√5. Therefore, x = ½ (3 ±√5).

4x2 + 12x + 5 = 4x2 + 2x + 10x + 5 = 2x(2x+1) + 5(2x+1) = (2x+1)(2x+5)

4x2 is 8+ 12x + 3 collect like terms, 8+3= 11, 12x+11 to solve for x, transpose the 11 to the other side of the = sign, 12x=-11, divide by 12, x=-11/12

4(x + 2)(x + 1)

(2x+5)(2x+1)

y=4x2+3x+8

4x2 plus 3=11

2(4x2 + 6x - 1)

4x2+49x+90 = (4x+9)(x+10) when factored

Jjg

As written, that's 4x squared = -21 and x equals the square root of -21/4. But if you meant that to be 12x, it factors out nicely to (2x + 3)(2x + 3) and x would equal -3/2

4x2 - 12x + 9 = 4x2 - 6x - 6x + 9 = 2x(2x - 3) - 3(2x - 3) = (2x - 3)(2x - 3) or (2x - 3)2

4x

-((4x + 1)(x - 1))

dont know sorry

No.

(12x2 + 18) / (3x2 + 6) = (4x2 + 6) / (x2 + 2)

You need to rivse your question. It appears that there is not an equation here. 4*2+12x+9? You can't really solve this it is more of a statement. You can however simplify it to 12x+17- Whoever wrote this obviously can't read. It's supposed to be 4x^2+12x+9 (2x+3)(2x+3)

If you mean: 4x squared+12x+9 then it is (2x+3)(2x+3)

People also asked